High-performance composite bridge deck with prestressed basalt fiber-reinforced polymer shell and concrete. (15th December 2019) - Wang, Xin; Peng, Zheqi; Wu, Zhishen; Sun, Shenpeng
Highlights: The composite deck with corrugated teeth exhibits superior integrated behavior. The composite deck can survive 10 million cycles under a load level of 0.439. The FE models can provide a reliable capacity value for regularly failed specimens. Abstract: In this study, a basalt fiber-reinforced polymer (BFRP) shell–concrete composite bridge deck with prestressed BFRP strips was investigated. The effectiveness of the prestressed shell was verified based on a preliminary study. Eight full-scale specimens were designed to examine the static and fatigue behaviors, including the failure modes, ultimate capacities, load–displacement curves of the bridge deck, and key areas of the BFRP shell and prestressed BFRP strips. The parameters of the bridge deck included the surface conditions, fiber layout of the shell, position of the reinforcement, and adoption of the prestressed BFRP strips. The theoretical formulas of the composite bridge deck were also derived. The results show that the composite decks exhibit excellent integrated behavior including high stiffness, high capacity, and reliable interfacial bonds. The specimen with adhered sand achieved an evidently higher stiffness and capacity than the control specimen. The corrugated teeth were beneficial for the stiffness but irrelevant for the ultimate capacity of the specimens. The layout of the fiber mat rather than that of the fiber filament in the BFRP shell could slightly enhance the ultimate capacity but not affect the stiffness. The arrangement of the longitudinal steel bars in the tension zone and stirrups in the deck could significantly enhance the stiffness and capacity of the deck, respectively. The fatigue test proved that this bridge deck could survive 10 million cycles under a load level of 0.439 and a load amplitude of 96.5 kN, for which the residual capacity and stiffness reduced by less than 8%. The finite element models could reflect the real failure process and yielded a reliable capacity value, whereas the theoretical formulas provided conservative results of the capacity and stiffness.